Impact of ankle arthrodesis on quality of life - da Silva, Fernando Cancella; Benevides, Wilel de Almeida; Silva, Thiago Alexandre Alves da; Monteiro, Luciana Silveira; Benevides, Pedro Costa (Scientific Journal of the Foot & Ankle, 2018)
Objective: To evaluate the quality of life of patients undergoing ankle arthrodesis through functional scores such as the American Orthopedic Foot & Ankle Society (AOFAS) scale adapted for the Portuguese language and the Medical Outcomes Study 36-Item Short-Form Health Survey (SF-36). Methods: A descriptive cross-sectional study was carried out between January 2005 and December 2016, with 26 patients undergoing ankle arthrodesis. Two quality of life assessment questionnaires were applied: the AOFAS in the pre- and postoperative period and the SF-36 in the postoperative period. Descriptive and analytical statistical analyses were performed using SPSS, version 23. Results: The main findings are related to the correlations of functional capacity (p=0.002; R²=0.42), limitation due to physical aspects (p=0.05; R²=0.19) and pain (p=0.006; R²=0.35) with age as the predictor and the correlation between preoperative AOFAS scores (p=0.03; R²=0.27) and the aetiology of arthrodesis as the predictor. Conclusion: Ankle arthrodesis is a procedure capable of improving the quality of life of the patient as a whole, including the physical, social, emotional and mental health aspects, rather than pain alone, which has been the main objective of the procedure until the present moment. Level of Evidence II; Prognostic Studies.